Obstetric iatrogenesis in the United States: the spectrum of unintentional harm, disrespect, violence, and abuse. Issue 2 (5th June 2021) - Liese, Kylea L.; Davis-Floyd, Robbie; Stewart, Karie; Cheyney, Melissa
Abstract: 'Medical iatrogenesis' was first defined by Illich as injuries 'done to patients by ineffective, unsafe, and erroneous treatments'. Following Lokumage's original usage of the term, this paper explores 'obstetric iatrogenesis' along a spectrum ranging from unintentional harm (UH) to overt disrespect, violence, and abuse (DVA), employing the acronym 'UHDVA' for this spectrum. This paper draws attention to the systemic maltreatment rooted in the technocratic model of birth, which includes UH normalized forms of mistreatment that childbearers and providers may not recognize as abusive. Equally, this paper assesses how obstetric iatrogenesis disproportionately impacts Black, Indigenous, and People of Color (BIPOC), contributing to worse perinatal outcomes for BIPOC childbearers. Much of the work on 'obstetric violence' that documents the most detrimental end of the UHDVA spectrum has focused on low-to-middle income countries in Latin America and the Caribbean. Based on a dataset of 62 interviews and on our personal observations, this paper shows that significant UHDVA also occurs in the high-income U.S., provide concrete examples, and suggest humanistic solutions.